Extrato etanólico de caroço de manga como antioxidante em rações para Suínos em crescimento e terminação - Araújo, Lina Raquel Santos (2017)
The objective was to evaluate the ethanolic extract of mango seed (EEMS) as antioxidant for pigs in the growth and finishing phases and its possible effects on performance, blood and serum parameters, carcass characteristics, meat and mortadella elaborated with the meat of these animals. Thirty-two castrated male pigs with 60 days of age and initial mean weight of 20.20 ± 1.34 kg were used in a randomized complete block design with 4 treatments and 8 replicates. The treatments consisted of the diets: control - without addition of antioxidants; BHT - with 200 ppm of butylhydroxytoluene (BHT); EEMS200 - with 200 ppm of EEMS; And EEMS400 - with 400 ppm of EEMS. Samples of the rations were evaluated for oxidative stability and antioxidant potential on the day of manufacture and 21 days later. Antioxidant added ratios showed better lipid stability and antioxidant potential than control. Animals fed rations containing 400 ppm EEMS showed greater weight gain up to 110 days of age (P <0.05). Pigs consuming ration containing 200 ppm of EEMS showed a reduction in the number of red blood cells (P <0.001) and higher mean corpuscular volume (P <0.0001), while those that consumed the control diet had a reduction in the mean corpuscular hemoglobin concentration in relation to the other treatments (P <0.01). The BHT added to the diet induced an increase in the number of leukocytes (P <0.01). The effect of the treatment interaction and day of collection (P <0.05) on lipid stability, phenolic compounds and antioxidant potential of the serum were observed, with the best results related to the animals that consumed EEMS-containing ration. The total antioxidant activity of the serum was not influenced by the treatments (P> 0.05). Animals that consumed ration containing 400 ppm of EEMS showed lower loss of liquid by cooking and higher values of reduced glutathione, phenolic compounds and total antioxidant activity in relation to the other treatments (P <0.0001). Regarding the antioxidant potential, higher values were found in the meat of animals that consumed added BHT ration and 400 ppm of EEMS in relation to the meat of pigs fed the control ration (P <0.01). The highest value of the L * component was recorded in the mortadellas made with the meat of animals that consumed the BHT rations when compared to those consuming rations containing 200 ppm of EEMS (P <0.05). Mortadellas made with the meat of animals that consumed ration containing 400 ppm of EEMS presented higher levels of phenolic compounds in relation to the other treatments at 60 days of storage. At 90 days, greater value was observed for mortadella formulated with meat from animals who consumed EEMS regardless of the inclusion level (P <0.0001). For the total antioxidant activity, it was verified higher values in the mortadellas elaborated with the meat of pigs that consumed ration with addition of BHT at the 30 days of storage, already at 60 days the addition of 400 ppm of EEMS was similar to the BHT and at 90 Days the two levels of EEMS were similar to BHT (P <0.001). It was concluded that EEMS can be used as an antioxidant in pig diets without altering carcass characteristics and blood parameters. The inclusion of EEMS at the 400 ppm level provides better performance of pigs up to 110 days of age, improves lipid stability, increases total phenolic compounds content and serum antioxidant potential, reduces liquid losses by cooking, increases reduced glutathione and the antioxidant potential of fresh meat and increases the content of phenolic compounds to the total antioxidant activity of raw and processed meat.